ISLAMIZATION OF KNOWLEDGE REVISITED: FROM IDEOLOGICAL AND APOLOGETIC MISREADINGS TO AN EPISTEMOLOGICAL RECONSTRUCTION - Mohammad Muslih; Fuad Muhammad Zein (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2026)
This article re-examines the concept of the Islamization of knowledge by positioning it as an epistemological project rather than merely an ideological, revivalist, or apologetic agenda – something that often appears in contemporary academic discourse. The aim here is to reconstruct the conceptual framework of Islamization through an analysis of the philosophical assumptions underlying both modern scientific structure and the Islamic worldview. Methodologically, this study draws on a qualitative approach grounded in conceptual-epistemological analysis to explore the relationship between worldview, epistemology, and the construction of knowledge in Islamic tradition and modernity. This study shows that Islamization cannot be reduced to a normative integration of religion and science. Instead, it has to be understood as an epistemological critique of modern scientific paradigms, and at the same time, as an effort to reconstruct a knowledge framework based on Islamic ontology, epistemology, axiology, and methodology. This study argues that Islamization represents an alternative epistemic model that seeks to rebuild the foundations of scientific knowledge in an integrative and reflective manner. The theoretical contribution of this article lies in repositioning the Islamization of knowledge within the broader framework of global epistemic polarity, both as a critique of knowledge and as a dialogical offer for scientific reconstruction.